Limit behavior of autonomous random oscillating system of third order - Borysenko, O.D.; Borysenko, O.V. (Інститут математики НАН України, 2007)
The asymptotic behavior of the general type third order autonomous oscillating system under the action of small non-linear random perturbations of ”white” and ”Poisson” types is investigated.